PERSEPSI MAHASISWA TENTANG KOMPETENSI KEPRIBADIAN DOSEN PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP-UIR PEKANBARU - Suryanti Suryanti; Sudarmi; Afnila Fitradini Har (UIR Press, 2020)
This study purposes to determine students’ perception regarding the lecturer personality competencies. The method of study is survey. Research instrument is using questionnaires, observation, interviews, and documentation. The population in this study was in third year, semester VI students (class A, B, C). The number of population is 106 students with high, medium, and low academic abilities in their third year semester VI. Sampling method is using saturated samples. Data analysis use descriptive method. The result of personality competency research, -with 5 indicator of high, medium and low academic abilities, for 1st indicator, which stated as act in accordance with the Norms of Religion, Law, Social and Culture of the Indonesian Nation, an average of 98.10 categories as very good, for indicator 2 stated as self portray as a person who is honest, noble, and exemplary for students and the community an average of 85.97 categories as very good. Indicator 3, which is showing yourself as a person who is steady, stable, mature, wise, and authoritative, on average 84.40 categories as very good. Indicator 4, demonstrates work ethic, high responsibility, pride in being a teacher, and self-confidence, on average 83.40 categories as very good. Indicator 5, mention as upholding the ethics code of the teaching profession, averaging in 78.75 as good categories.